Total elbow arthroplasty following complex fractures of the distal humerus: results in patients over 65 years of age. - Pogliacomi, Francesco; Schiavi, Paolo; Defilippo, Massimo; Corradi, Maurizio; Vaienti, Enrico; Ceccarelli, Francesco; Rotini, Roberto; Calderazzi, Filippo (Acta Biomedica Atenei Parmensis, 2016)
Background: The treatment of complex distal humerus fractures is challenging and is often associated with unsatisfactory results. Anatomic reduction and stable internal fixation is difficult to obtain, especially in elderly osteoporotic patients. For these reasons, total elbow arthroplasty (TEA) has recently evolved as a valid procedure in selected cases following these injuries. The aim of this study was to analyze outcomes of TEA for the treatment of complex distal humerus fractures in 20 low-demanding patients over 65 years of age. Materials and methods: All patients, at a mean follow-up of 60 months, were evaluated clinically using the Mayo Elbow Performance Score (MEPS) and radiographically in order to assess the positioning of the prosthetic components and signs of loosening. Statistical analyses investigated the presence of clinical and radiographic variables as predictive factors of poor functional outcomes. Results: Similar MEPSs were observed in the affected and unaffected arm. Results were good or excellent in 90% of the patients, even if a high rate of complications (35%) was encountered. The development of postoperative complications and concomitant cognitive impairment and rheumatoid arthritis were predictive factors of unsatisfactory outcomes. Conclusions: According to the results observed, TEA can be considered as a valid treatment for complex fractures of the distal humerus in low-demanding patients older than 65 years of age, in which a stable fixation is difficult to obtain. Several variables may influence the final outcomes.